Penggunaan Media Sosial sebagai Sarana Promosi Bisnis Pasca Pandemi Covid-19 - Beni, Sabinus; Clara, Novelni (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2024)
The Covid-19 pandemic had a significant impact on various sectors, including entrepreneurial businesses. In this situation, the use of social media as a promotional tool has become increasingly important in sustaining and developing their businesses. This research aims to analyze the influence of the Covid-19 pandemic on student entrepreneurial businesses at Shanti Bhuana Institute and to explore the use of social media as a promotional tool in overcoming the challenges during the pandemic Additionally, the challenges of utilizing social media as a promotional tool need to be examined. This research adopts a qualitative approach, collecting data through in-depth interviews with a number of student entrepreneurs at Shanti Bhuana Institute. The data is analyzed using content analysis methods to identify the impacts of the pandemic and strategies for using social media. The findings indicate that the Covid-19 pandemic has had negative effects on student entrepreneurial businesses, including a decline in revenue and demand. However, the use of social media as a promotional tool provides opportunities to reach a wider audience and build customer relationships. Student entrepreneurs employ strategies such as creating engaging content, collaborating with influencers, and actively interacting with customers through social media